2017
DOI: 10.3390/nu9111225
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Legislation on Dietary Products for Sportspeople in a European Framework

Abstract: The consumption of nutritional ergogenic aids is conditioned by laws/regulations, but standards/regulations vary between countries. The aim of this review is to explore legislative documents that regulate the use of nutritional ergogenic aids intended for sportspeople in a Spanish/European framework. A narrative review has been developed from official websites of Spanish (Spanish Agency of the Consumer, Food Safety, and Nutrition) and European (European Commission and European Food Safety Authority) bodies. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
0
27
0
5
Order By: Relevance
“…The obtained results regarding the place where the SS are bought contradict the current data since the current trend is online shopping [23,28]. The participants of the present study, regardless of sex and the level of competition, are more inclined to buy in specialized stores and pharmacies mainly, where they can also find more professional advice compare to online shopping, which decreases the possibilities of purchasing lower-quality or illegal products, with lesser guarantees due to the absence of specific legislation in Europe or other countries, contributing to misleading advertising [39,46]. This topic is related to the person or source that generates or advises the use of SS.…”
Section: Discussionmentioning
confidence: 95%
“…The obtained results regarding the place where the SS are bought contradict the current data since the current trend is online shopping [23,28]. The participants of the present study, regardless of sex and the level of competition, are more inclined to buy in specialized stores and pharmacies mainly, where they can also find more professional advice compare to online shopping, which decreases the possibilities of purchasing lower-quality or illegal products, with lesser guarantees due to the absence of specific legislation in Europe or other countries, contributing to misleading advertising [39,46]. This topic is related to the person or source that generates or advises the use of SS.…”
Section: Discussionmentioning
confidence: 95%
“…In relation to this, the data obtained in the present study support this theory, given that the DS purchasing preferences for the sample were mostly online (45.6%), which was more frequent in professional players (54.1% vs. 33.3%; OR = 1.40 [1.01–1.94]). Purchasing DS in this way may lead to health and/or performance risks due to biased and unreliable information from this source [ 27 , 29 , 34 ], discovering pharmacological substances not declared on the label [ 49 , 50 ], which is inappropriate with respect to the optimal protocol [ 51 , 52 , 53 ], or lack of specific legislation [ 45 , 50 ]. To enhance control and monitorisation, it is necessary to promote a specific legislation about DS in sport, as many studies have revealed that consumers are unaware of what they are taking and are even consuming DS or ingredients included in them that are prohibited or harmful to health [ 45 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…ISSN (9) Ergogenic aid for power/strength athletes to help them optimise training adaptations or athletes who need to sprint intermittently and recover during competition (e.g. American football, soccer, basketball, tennis, etc.).…”
Section: No Datamentioning
confidence: 99%
“…Of these, only seven declarations fully or partially complied with that established by the relevant institutions, consensus documents or scientific evidence. These declarations are approved at a European level by the EFSA and the EC, the latter having specific legislation to regulate these products (9,15,28) . As indicated, only in the case of the claims 'Improves strength', 'Increases muscle mass', 'Enhances physical performance', 'Increases power', 'Enhances physical performance in adults over the age of 55', 'Promotes the replacement of creatine stores' and 'Replenishes muscle glycogen stores', their adequacy was confirmed.…”
Section: Health Claims and Proposed Dosagesmentioning
confidence: 99%
See 1 more Smart Citation